Failure of Repeated Treatment With Praziquantel and Arthemeter in Four Patients With Acute Schistosomiasis. Issue 2 (24th January 2014) - Praticò, Liliana; Mariani, Bianca; Brunetti, Enrico; Maserati, Roberta; Bruno, Antonella; Novati, Stefano; Chichino, Guido
Abstract : Schistosomiasis is on the rise but still difficult to treat in international travelers; it should be suspected in patients returning from endemic areas. Praziquantel (PZQ) is not effective and may aggravate symptoms. More recently, combination treatment with artemisinin derivatives have shown promising results. We report four cases of acute schistosomiasis (AS) in which several courses of combined therapy had been necessary to obtain negative serology.